Parental Involvement Influence on Education Participation for Learners with Hearing Impairments in Special Public Primary Schools in Meru an d Isiolo Counties- Kenya - Karegi Nthuku, Purity; Kibaara M, Tarsilla; Kinoti M’Ngaruthi, Timothy (2024)
Globally need for education, as a measure of one's ability to function fully in today's society, is an important motivator for efforts to ac hieve the highest level of education in the world. The persistent unde r achievement of deaf students in Kenyan schools is of great concern a s evidenced by final average scores in their formative and summative s cores in their assessments. This study aimed to find out how parental involvement influences education participation for learners with heari ng impairment. The study was guided by Maslows theory of motivation in learning. A phenomenological research design was utilized. The study targeted three primary schools handling learners with hearing impairme nts in Meru and Isiolo counties that is Kaaga, Njia, and Isiolo school for learners with hearing impairment. A thematic approach was used to analyze the qualitative data. The study revealed that parental involv ement was minimal. Based on the study findings, collective effort shou ld be made to sensitize the parents on their roles in the education of their children. Employers of parents of students with hearing impairm ents should be given days off with pay when going to attend to their c hildren's issues in school like closing days, opening days, and clinic days for their children. The school should provide some incentives to parents like meals during the school meetings to help reduce parents’ expenses. The government should ensure tax waivers for parents of stu dents with hearing impairments. The stakeholders should help change pa rental attitudes that their children will not make it.